Subtraction of negative number is done by converting the subtraction problem to an addition problem.
For example: 7 - (-4) = The first "-" sign means subtraction. The second "-" sign means a negative number. The problem is done in the following way.
7 - (-4) becomes 7 + (+4) and the answer is 11 So we change the subtraction
sign to an addition sign and change the sign of the number that comes immediately
after the subtraction sign. Then we treat the problem as an addition problem and use the rules of addition to solve the problem.
Try this problem: 8 - (-6) = answer
Try this problem: 9 - (+5) = answer
Follow the rules and try this problem -7 - (-3) = answer
Try thinking of subtraction problems in this way. Let say you owe $14. We represent the $14 debt as a -$14. The person you owe the $14 too says you only have to repay $10. She has taken a -$4 debt away from you.
So -$14 - (-$4) = -$10 To use the rule we would write it this way
-$14 - (-$4) = -$14 + (+4) = -$10